2014
DOI: 10.1111/jsm.12587
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Is an Independent Predictor of Severe Lower Urinary Tract Symptoms and of Erectile Dysfunction: Results from a Cross-Sectional Study

Abstract: Introduction Several studies have linked the association between lower urinary tract symptoms (LUTS), erectile dysfunction (ED), and the presence of insulin resistance (IR) due to an underlined metabolic syndrome (MetS). Aim This study aims to determine the relationship between IR, sexual function, and LUTS and to demonstrate the ability of IR in predicting ED and severe LUTS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
2
34
1
Order By: Relevance
“…[2][3][4][5] Evidence supports a strong causal link between IR and ED. [6][7][8][9][10] In fact, ED has been considered an early clinical manifestation of risk factors for cardiovascular events including acute myocardial infarction. 11 In addition, ED may be the first clinical sign of IR in young men.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] Evidence supports a strong causal link between IR and ED. [6][7][8][9][10] In fact, ED has been considered an early clinical manifestation of risk factors for cardiovascular events including acute myocardial infarction. 11 In addition, ED may be the first clinical sign of IR in young men.…”
Section: Resultsmentioning
confidence: 99%
“…We have also recently shown that serum insulin increases were associated with greater severity of LUTS-BPH and ED [15]. It is plausible that insulin levels determine a lower synthesis and release of NO, owing to lower activity and expression of NO synthase, which is combined with an accelerated consumption of NO [16].…”
Section: Discussionmentioning
confidence: 96%
“…LUTS were evaluated by culturally and linguistically validated versions of the IPSS. LUTS severities were classified as mild (IPSS 0-7), moderate (IPSS [8][9][10][11][12][13][14][15][16][17][18][19] and severe . The short form of the International Index of Erectile Function (IIEF) questionnaire was used for the assessment of patients' erectile function and the presence of ED was considered to be IIEF-erectile function <26 [14].…”
Section: Methodsmentioning
confidence: 99%
“…16,17 The aim of this study was to verify whether ED, as objectively defined by the International Index of Erectile Function (IIEF-5), is associated with increase of comorbidities, calculated with the Charlson comorbidity index (CCI) and LUTS, defined by the IPSS.…”
Section: Introductionmentioning
confidence: 99%